Motivation in academic performance - Moreira-Morales, Denny Beatriz; García-Loor, María Inés (International research journal of management, IT and social sciences, 2024)
Motivation is an essential component of the educational process, which influences learning: what, when and how one learns, contributing to academic performance. The study was developed in the field of psych pedagogy, the objective was to analyze motivation in academic performance, in its development the importance of motivation in the school environment is diagnosed, motivating methodologies in the teaching-learning process are analyzed, and They identify methodologies that favor academic performance. The applied methodology has a mixed approach, it is based on the collection of specialized information on motivation and academic performance, it is descriptive and field, and the data is collected from primary sources of the “Bachillero” Educational Unit. Inductive, analytical, synthetic, and statistical methods and survey, interview and observation techniques are used. The study population is made up of students, teachers and directors, the intentional sample corresponds to 37 people made up of 30 students from the Eighth Basic Year, 6 teachers and the director of the Bachillero Educational Unit. The results show the contribution that motivation generates in academic performance.